Investigate the effectiveness of bio-silica absorbent from several sarawak palm oil waste ash - Ummie Zulaikha, Binti Kamarul Jaman (Universiti Malaysia Sarawak (UNIMAS), 2017)
Due to the high production of palm oil, surplus quantities of palm oil biomass waste such as empty fruit bunches (EFB), palm kernel shell (PKS), and oil palm decanter cake (DC) are generated. Currently, to solve the waste disposal issues in palm oil industries, these wastes are used as fuel to generate steam for boilers, which end up as ash. As these wastes are rich with silica content, thus this study aims to study the potential of bio-silica extracted from EFBs,PKSs, and DCs ashes as moisture absorbent. Several analysis were conducted to study the characteristics and the amount of silica in EFB, PKS, and DC ashes at different combustion temperatures of 400°C to 800°C. Prior to the process, EFBs, PKSs, and DCs undergo acid leaching process using 1M citric acid to remove impurities and increase silica yield in the extraction process. The characteristic analyser of the ash include colour analysis, weight analysis, Fourier Transform Infrared (FTIR), Brunauer-Emmet-Teller (BET), and Scanning Electron Microscopy (SEM). For the extraction process, the treated EFBs, PKSs, and DCs ashes produced at temperature 800°C are chosen as it contains the highest amount of silica, and are gellified and continued with aging time of 1 and 2 hours to produce moisture absorbent. The characteristic analyser of extracted bio-silica in EFB, PKS, and DC include FTIR, BET, SEM, and Energy Dispersive X-Ray (EDX). SEM images of the extracted bio-silica give irregular shape particles with porous texture. From FTIR result, a dominant peak between 950 cm-1 to 1150 cm-1 was detected on all extracted bio-silica samples which refers to silicate (Si-O) functional group. From EDX result, bio-silica EFB 2-hours, PKS 2-hours, and DC 2-hours, has high percentage of element mass compared to 1 hour for all the samples. Meanwhile for BET, PKS 2-hours has the highest surface area, which is 14.037 m2 /g and based on the capability test it had perform closely to the pure silica made from natural quartz. It is recommended exploring bio-silica in the sample by using XRD and improve the extracted bio-silica absorption performance.